2014
DOI: 10.1161/strokeaha.113.003168
|View full text |Cite
|
Sign up to set email alerts
|

Upper Limb Recovery After Stroke Is Associated With Ipsilesional Primary Motor Cortical Activity

Abstract: Background and Purpose-Although neuroimaging studies have revealed specific patterns of reorganization in the sensorimotor control network after stroke, their role in recovery remains unsettled. To review the existing evidence systematically, we performed activation likelihood estimation meta-analysis of functional neuroimaging studies investigating upper limb movement-related brain activity after stroke. Methods-Twenty-four studies using sensorimotor tasks in standardized coordinates were included, totaling 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
112
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(130 citation statements)
references
References 54 publications
10
112
2
1
Order By: Relevance
“…A recent study shows evidence that DTI measures may be used as potentially predictive of individual recovery in stroke patients receiving newer neurorehabilitative therapies, such as transcranial direct current stimulation (Lindenberg et al, 2012). Besides DTI, fMRI is another non-invasive neuroimaging technique that has been used to gain better understanding of the processes of brain functional reorganization accompanying motor recovery after stroke (Calautti and Baron, 2003; Riecker et al, 2010; Garrison et al, 2013; Havsteen et al, 2013; Favre et al, 2014; Zhang et al, 2014). Measures derived from fMRI have also been shown as potential biomarkers to track recovery, with correlations between functional changes and fMRI measures demonstrated with treatments such as Brain-Computer Interface (BCI) therapy (Mukaino et al, 2014), constrain-induced movement therapy (Murayama et al, 2011; Kononen et al, 2012) and motor imagery therapy (Sun et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study shows evidence that DTI measures may be used as potentially predictive of individual recovery in stroke patients receiving newer neurorehabilitative therapies, such as transcranial direct current stimulation (Lindenberg et al, 2012). Besides DTI, fMRI is another non-invasive neuroimaging technique that has been used to gain better understanding of the processes of brain functional reorganization accompanying motor recovery after stroke (Calautti and Baron, 2003; Riecker et al, 2010; Garrison et al, 2013; Havsteen et al, 2013; Favre et al, 2014; Zhang et al, 2014). Measures derived from fMRI have also been shown as potential biomarkers to track recovery, with correlations between functional changes and fMRI measures demonstrated with treatments such as Brain-Computer Interface (BCI) therapy (Mukaino et al, 2014), constrain-induced movement therapy (Murayama et al, 2011; Kononen et al, 2012) and motor imagery therapy (Sun et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…57,105,126 Similarly, for stroke, activation of the ipsilateral primary motor cortex has been associated with both good and poor behavioural outcomes. 114 Such variability can render the physiological significance of t-fMRI differences unclear.…”
Section: T-fmri Results Are Variablementioning
confidence: 99%
“…106,114 Reproducibility studies have demonstrated that even well-controlled longitudinal t-fMRI studies of normal subjects likely have a high degree of intrasubject measurement error 131 and require at least 20 subjects per group to perform reliable and sensitive group analyses. 97 The higher degree of variability seen within brain injury cohorts means that required numbers are likely to be substantially higher.…”
Section: T-fmri Results Are Variablementioning
confidence: 99%
See 2 more Smart Citations